Determinación de la influencia de las vibraciones verticales en los principales modos de falla de una broca tricónica (2017)
To describe the causes of the main failure modes in triconic drills due to vertical vibrations, this research proposed a computational model by the finite element method that is developed through a methodology that includes from modal analysis to dynamic analysis, In order to find the efforts of those suffered in the drill by the vertical vibrations. The approach given by this type of drills presents a greater probability of affectation by axial vibrations; In addition to analyzing the drill - formation interaction, taking into account the presence of drilling fluids and the mechanical properties of the formation for the understanding of the vibratory phenomenon. Thus, the results of the research validate the information obtained through the bibliographic review as to what the axial displacement is among the values ​​of the literature, also supports the hypothesis that the applied load on the surface and the displacement in The inversely proportional variables.